Vitamin D and circulating tumor cells in primary breast cancer - Mego, Michal; Vlkova, Barbora; Minarik, Gabriel; Cierna, Zuzana; Karaba, Marian; Benca, Juraj; Sedlackova, Tatiana; Cholujova, Dana; Gronesova, Paulina; Kalavska, Katarina; Pindak, Daniel; Mardiak, Jozef; et al. (Frontiers in Oncology, 2022)
Background: Circulating tumor cells (CTCs) contribute to the metastatic cascade and represent an independent survival predictor in breast cancer (BC) patients. Vitamin D has pleiotropic effects and its low concentrations are associated with breast cancer and metastasis. The aim of this study was to assess plasma vitamin D in primary BC patients in relation to CTCs Methods: This study included 91 non-metastatic BC patients (stage I-III). Blood samples for the analyses were drawn at the time of surgery. CTCs were assessed using a quantitative RT-PCR assay for expression of epithelial (CK19) or epithelial-mesenchymal transition (EMT) genes (TWIST1, SNAIL1, SLUG, ZEB1). Total 25-OH vitamin D was measured in plasma using ELISA. Results: CTCs were detected in 30 (33%) patients. Patients with detectable CTCs in peripheral blood had significantly lower vitamin D concentrations in comparison to patients without detectable CTCs (mean ± SD) 8.50 ± 3.89 µg/L for CTCs positive vs. 9.69 ± 3.49 µg/L for CTCs negative patients respectively, P = 0.03). There was no association between plasma vitamin D and other patient/tumor characteristics. Patients with vitamin D above median had a better overall survival (HR = 0.36, 95%CI 0.16 – 0.80, P = 0.017). Conclusions: Low vitamin D could be a consequence and hence a biomarker of a more invasive disease. Alternatively, vitamin D could be associated with survival because of its role in tumor dissemination. Whether its supplementation affects the metastatic cascade should be tested in animal experiments and interventional studies.